Nanostructured biosensor for detecting glucose in tear by applying fluorescence resonance energy transfer quenching mechanism - Chen, Longyi; Tse, Wai Hei; Chen, Yi; McDonald, Matthew W.; Melling, James; Zhang, Jin (Biosensors & bioelectronics, 2017)
In this paper, a nanostructured biosensor is developed to detect glucose in tear by using fluorescence resonance energy transfer (FRET) quenching mechanism. The designed FRET pair, including the donor, CdSe/ZnS quantum dots (QDs), and the acceptor, dextran-binding malachite green (MG-dextran), was conjugated to concanavalin A (Con A), an enzyme with specific affinity to glucose. In the presence of glucose, the quenched emission of QDs through the FRET mechanism is restored by displacing the dextran from Con A. To have a dual-modulation sensor for convenient and accurate detection, the nanostructured FRET sensors were assembled onto a patterned ZnO nanorod array deposited on the synthetic silicone hydrogel. Consequently, the concentration of glucose detected by the patterned sensor can be converted to fluorescence spectra with high signal-to-noise ratio and calibrated image pixel value. The photoluminescence intensity of the patterned FRET sensor increases linearly with increasing concentration of glucose from 0.03mmol/L to 3mmol/L, which covers the range of tear glucose levels for both diabetics and healthy subjects. Meanwhile, the calibrated values of pixel intensities of the fluorescence images captured by a handhold fluorescence microscope increases with increasing glucose. Four male Sprague-Dawley rats with different blood glucose concentrations were utilized to demonstrate the quick response of the patterned FRET sensor to 2µL of tear samples. •The nanostructured biosensor is designed for dual detection of tear glucose.•Fluorescence intensity increases linearly with glucose level from 0.03 to 3mM.•Image pixel intensity value of the sensor is corresponding to the glucose level.•Animal test indicates the sensor can measure 2µL tear glucose in 30s.